Economic Factors Influencing Healthcare Access and Health Outcomes Among Residents of Salaama Parish, Makindye Division, Kampala. A cross-sectional study. - Mark Kaukira; Rogers Talemwa (Student's Journal of Health Research Africa, 2026)
Background: Income levels and employment status are significant determinants of healthcare access. Low-income households are more likely to delay or forgo healthcare due to financial constraints. The study aims to investigate the economic factors impacting health outcomes in Salaama Parish. Methodology: The study employed a cross-sectional design with both quantitative and qualitative components. The sample size for this study was calculated using Slovin's formula, resulting in a sample size of 100 participants. Data verification was also conducted to re-check data against sources, validate data entry, and ensure data consistency. Double data entry and automated checks for errors and inconsistencies were used to ensure data entry quality. Results: Financial constraints significantly limited healthcare access among respondents. Fifty-two per cent reported that financial difficulties always or often affected their ability to seek care, while 74% had delayed or avoided healthcare because of costs. Additionally, 76% could not afford medications and routine checkups. Health insurance coverage was low, with only 10% insured, mainly through private insurance. Among uninsured respondents, lack of awareness (27%) and limited availability (14%) were major barriers. Although 48% rated their healthcare access as good or very good, 46% reported insufficient income despite employment, while 35% identified unemployment as a barrier. Furthermore, 78% believed their living conditions affected their health. 57% of respondents were female, while 43% were male. Conclusion:Economic factors significantly hinder healthcare access in Salaama Parish, particularly through financial constraints, inadequate income, unemployment, and limited insurance coverage. Strengthening affordable healthcare programs and financial protection for vulnerable groups is essential to improve healthcare access and health outcomes. Recommendations: Economic barriers to healthcare access can be significantly reduced by implementing affordable, government-subsidised healthcare programs targeting vulnerable groups like children, pregnant women, and the elderly.